Efficient and selective cleavage of the tert-butoxycarbonyl (Boc) group under basic condition - Mohapatra, Debendra K.; Durugkar, Kulbhushan A. (Arkivoc, 2005)
A simple, efficient and mild method for the selective cleavage of tert-butoxycarbonyl (Boc) from dicarbamates and a carbonyl or aromatic ring in conjugation with the nitrogen atom bearing the Boc-group is described under basic condition.
Keywords: alpha-amino acids; celogenitins; di-t-butylimidodicarbonate; racemization; Selective deprotection